Compliance of enhanced recovery after surgery (ERAS) protocol in emergency and elective colorectal cancer surgery with a perspective from a developing country - Muneeb Ullah; Muhammad Kashif Khan; Aqsa Adeel; Muhammad Faisal Murad; Adil Shafi (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate compliance with enhanced recovery after surgery protocol of patients undergoing colorectal carcinoma surgery, and to compare its effect on outcomes. Method: The retrospective study was conducted at the Maroof International Hospital, Islamabad, Pakistan, and comprised data from July 15, 2016, to March 20, 2022, of patients of either gender undergoing elective or emergency colorectal carcinoma surgery. Data included age, gender, tumour site, type of surgery, surgical approach, compliance with each of the 25 components of the enhanced recovery after surgery protocol, length of hospital stay, surgery duration, 30-day readmission rate and perioperative mortality. Data was analysed using SPSS 23. Results: Of the 96 patients with mean age 50.03±14.86 years (range: 20-79 years), 65(67.7%) were males, 70(72.91%) were aged at least 40 years, and 75(78.12%) underwent elective surgery. Most common tumour site was rectum and sigmoid 49(51%). Laparoscopic surgery was performed in 17(17.7%) patients. No compliance was seen with carbohydrate loading of patients or limiting use of opioids in standard anaesthesia protocol. No nutritional supplementation was started from postoperative day 1. Mean compliance with all the protocol components was 74.9%±37.652 for both elective and emergency cases. Mean duration of surgery was 192.50±75.33 minutes, while mean length of hospital stay was 5.52±1.57 days. Re-admission within 30 days was needed in 2(2.1%) cases. There was no perioperative mortality. Conclusions: Better compliance with enhanced recovery after surgery protocol resulted in better perioperative outcomes. Key Words: Colorectal, ERAS, Compliance, Length of stay, Morbidity.